PENGARUH PENERAPAN BAHAN AJAR FISIKA TERINTEGRASI NILAI KARAKTER DALAM MODEL LEARNING CYCLE 7E TERHADAP HASIL BELAJAR SISWA KELAS XI DI SMAN 4 BUKITTINGGI - Liza Nellya Basviani (Universitas Negeri Padang, 2014)
Instructional materials integrate in schools have not character building. In other hand, the goverment mandates to integrate character ​​in school. The purpose of research is investigation implementasion effect of physics instructional materials with integration character building in the learning cycle 7E model to the learning outcomes of students on grade XI SMAN 4 Bukittinggi. The type of research is a quasi experimental with the randomized Only Control Group Design. The population of reseach was all class XI SMAN 4 Bukittinggi enrolled in 2013/2014 academic year. Sampling was done by purposive sampling technique with XI IPA1 and class XI IPA2 chosen as samples. The research instrument are the objective test for cognitive learning outcomes, observation sheets to affective and psychomotor domains. Data analysis use t-test at the 0.05 significance level for the cognitive, affective and psychomotor. Base on data analysis, implementasion of physic intructional materials with integration character building in learning cycle 7E model have significant effect to learning outcomeS of student on grade XI SMAN 4 Bukittinggi